Night Illumination, Tower of Jewels (Souvenir Guide Publishers)
Note On verso: Designed by Messrs. Carrere and Hastings, of New York, this, the Main Tower, rises to a height of 433 feet. In cold weather it is said to be four inches shorter than in warm weather, owing to the contraction of the steel. The arch is 110 feet height and 60 feet broad. The tower is in seven sections, surmounted by the Earth.